HUBUNGAN PEMBERANTASAN SARANG NYAMUK (PSN) DAN KEBIASAAN KELUARGA DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KOTA PONTIANAK TTAHUN 2013 - ., Ririn Sumantri (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Dengue Hemorragic fever (DHF) is an infection deseasescaused by dengue virus through vector of Aedes aegypti mosquito.Kalimantan Barat province had the largest cased caused by DBD inPontianak city. Numbers of DBD cases in 2009 is 3.893. Objective: Theaims of this research are to find out the relationship of mosquitos nestelimination including covering the water container, draining the watercontainer, burying unused things, not hanging clothes,using the mosquitonet, using repellent and temephos, and raising a wiggler eating fish towardthe occurrence of DHF in Pontianak at 2013. Methods: This research wasobservasional analytic research applying case-control design. This researchconducted in June 2014. Total population of this research was 100 samples,separated into two subject, 50 each control and case . Data had beencollected with the questionnaire instrument. Consecutive sampling used forcase and perposive sampling for control as sampling. Data had beenanalyzed with Chi Square technique test. Result: The results showed thatthere are a significant relationship towards DHF were draining the bathingcontainer (p= 0,002), covering the water container (p= 0,000), using repellent(0,001) and temephos using (p= 0,000). Multivariate analysis result showedthat probability of an individual with DHF if do not draining the watercontainer,using repellent and temephos is 92%. Conclusion: Covering thebathing container, draining the water container, using repellent and temephos using had a significant relationship towards the occurrence of DHF .Keywords: Dengue Hemorragic Fever, DHF Preventive Behavior,Occurrence of DHF1. Medical Education Program, Faculty of Medicine, Tanjungpura University, Pontianak, West Kalimantan2. Department of Public Health, Medical Education Program, Faculty of Medicine, Tanjungpura University, Pontianak, West Kalimantan3. Department of Histology, Medical Education Program, Faculty of Medicine, Tanjungpura University, Pontianak.